Dental, Skeletal, and Soft Tissue Changes after Bone-Borne Surgically Assisted Rapid Maxillary Expansion: A Systematic Review and Meta-Analysis - Christina Sekertzi; Maria-Marina Koukouviti; Athina Chatzigianni; Olga-Elpis Kolokitha (MDPI AG, 2023)
(1) Background: For non-growing patients with marked transverse maxillary deficiency, bone-borne surgically assisted rapid maxillary expansion (SARME) has been proposed as an effective treatment option. Objective: To evaluate the dental, skeletal, and soft tissue changes following bone-borne SARME. (2) Methods: An unrestricted systematic electronic search of six databases, supplemented by manual searches, was performed up to April 2023. The eligibility criteria included prospective/retrospective clinical studies with outcomes pertaining to objective measurements of dental/skeletal/soft tissue effects of bone-borne SARME in healthy patients. (3) Results: Overall, 27 studies satisfied the inclusion criteria. The risk of bias of the non-randomized trials ranged between moderate (20) and serious (4). For the two RCTs, there were some concerns of bias. Trials with outcomes measured at the same landmarks within the scope of the prespecified timeframe were deemed eligible for quantitative synthesis. Eventually, five trials were included in the meta-analysis. SARME was associated with a statistically significant lengthening of the dental arch perimeter immediately after expansion, along with a marginally significant decrease in palatal depth during the post-SARME retention period. Post-treatment SNA values exhibited no statistically significant change. (4) Conclusion: Current evidence indicates that bone-borne SARME constitutes an effective treatment option for adult patients with maxillary transverse deficiency. Further long-term randomized clinical trials with robust methodology, large sample sizes, and 3D evaluation of the outcomes are needed.